MANAJEMEN HIPOGLIKEMIA PADA PASIEN DENGAN GAGAL GINJAL KRONIS STAGE V: SEBUAH STUDI KASUS: MANAGEMENT OF HYPOGLYCEMIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE STAGE V: A CASE REPORT - Rizkiani, Agni; Pahria, Tuti; Nursiswati (STIKes Mitra Keluarga, 2025)
Introduction: Glucose homeostasis greatly affects CKD patients, who are at high risk for hyperglycemia and hypoglycemia. The risk of hypoglycemia is increased due to several factors, namely renal gluconeogenesis failure, impaired renal insulin breakdown, imperfect insulin degradation due to uremia, increased erythrocyte glucose uptake during hemodialysis, impaired counterregulatory hormone responses, nutritional deficiencies, and variability in exposure to antihyperglycemic agents and the effects of exogenous insulin. This study aims to identify the effect of hypoglycemia management in patients with chronic kidney disease who experience decreased blood glucose. Method: This study uses a case report method with a nursing care approach with interventions for unstable blood glucose levels, namely hypoglycemia management to overcome hypoglycemia. Result: Hypoglycemia management is evaluated by the results of the GDS examination and increased meal portions. After the intervention, there was an improvement in the GDS value on the second day of treatment, the increase in meal portions increased on the third day of treatment and signs of hypoglycemia were gone. Conclusion: In this case study indicate that hypoglycemia management intervention in the form of collaboration of 40% dextrose fluid administration in CKD patients experiencing hypoglycemia is an effective option to prevent further complications due to hypoglycemia.